2019
DOI: 10.1038/s41598-019-55338-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association study of 5 agronomic traits in olive (Olea europaea L.)

Abstract: Olive (Olea europaea L.) is one of the most economically and historically important fruit crops worldwide. Genetic progress for valuable agronomic traits has been slow in olive despite its importance and benefits. Advances in next generation sequencing technologies provide inexpensive and highly reproducible genotyping approaches such as Genotyping by Sequencing, enabling genome wide association study (GWAS). Here we present the first comprehensive GWAS study on olive using GBS. A total of 183 accessions (FULL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 97 publications
2
30
1
Order By: Relevance
“…Remarkably, we did not find any gene related to fatty acid metabolism and accumulation, although this has presumably been one of the most important characters under selection in olive domestication. Moreover, a recent study found 19 genes associated with five important agronomic traits in olive [ 61 ], and despite 14 of them being found in cv. Farga (see Additional file 2 : Table S16), only five were found in the gene set with negative Tajima’s D, and none was present in the detected selective sweep regions or the genes under positive selection according to MK test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, we did not find any gene related to fatty acid metabolism and accumulation, although this has presumably been one of the most important characters under selection in olive domestication. Moreover, a recent study found 19 genes associated with five important agronomic traits in olive [ 61 ], and despite 14 of them being found in cv. Farga (see Additional file 2 : Table S16), only five were found in the gene set with negative Tajima’s D, and none was present in the detected selective sweep regions or the genes under positive selection according to MK test.…”
Section: Resultsmentioning
confidence: 99%
“…In general, genes positively selected in cultivated olives were associated with a response to biotic and abiotic stresses. Interestingly, five genes detected with negative Tajima’s D are related to genes recently described as important for fruit weight and stone weight [ 61 ]. However, further analyses are needed to ascertain whether they indeed play a role in trait selection during domestication (see [ 74 ] for secondary compounds).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, we did not find any gene related to fatty acid metabolism and accumulation, although this has presumably been one of the most important characters under selection in olive domestication. Moreover, a recent study found 19 genes associated with 5 important agronomic traits in olive (59) and despite 14 of them being found in Farga (see Additional file 2: Table S8), none was present in the detected selective sweep regions. Similarly, a study based on transcriptomes of 68 different wild and cultivated samples using statistical approaches (PCAdapt (60) and BayeScan (61)) failed to identify candidate genes under selection associated with oil content or fruit size (11).…”
Section: Identification Of Genes Under Selectionmentioning
confidence: 97%
“…Other studies have also shown promising applications of transfer learning in materials informatics. [18,[34][35][36][37][38][39][40][41] In this study, we applied a specific type of transfer learning using pre-trained neural networks. For a target property, a neural network pre-trained on proxy properties is available in the library, where the source datasets are sufficiently large.…”
Section: Full Papermentioning
confidence: 99%